UN crash safe vehicle design using human body models. - Duarte, Marcelo Rubens Galdiano (2021)
This dissertation presents the design of a Safe Urban Vehicle capable of meeting the vehicle safety requirements established by the United Nations Economic Commission for Europe,UNECE. The electric vehicle was developed to be used on urban environments, having two seats and space for shopping and small luggage transportation. The design evaluation was performed through the explicit Finite Element Method. First it was analyzed the frontal impact crash test, based on ECE R94, where the model crashes a deformable barrier with 40% width offset. This simulation was realized using the traditional models of Anthropomorphic Test Devices (ATD), usually called dummies. It was analyzed the models body and head responses and the results were compared to the values required by the regulation. After that it was analyzed the car to pedestrian crash test based on regulation ECE R127. In this analysis the usual dummies were replaced by complex anthropomorphic devices based on human body containing tendons, bones and organs. Models obtained results were analyzed and the values were compared to the ones required by the regulation. Numerical tests were also executed to evaluate the performance of the vehicle in a lateral collision against a rigid pole based on ECE R135. In this simulation it was used the 50% World Side Impact dummy and it was evaluated models responses of the head, thorax and shoulders. The dissertation also presents a discussion about the difficulties found in the simulations and how they could be overcome.